Mergers and Acquisitions in the Container Shipping Industry - Divyaranjani R (International Journal of Supply Chain Management, 2018)
This article analyzes the Industrial dimensions between acquiring and target firms taken into the significant of merger and acquisitions transactions.Mergers and Acquisitions activities were more intense among firms located closely each other. Mergers and acquisition transactions are a value creating activity within shipping industry firms before and after the merger and who benefits from this activity. While the existing article suggests that the smaller and unquoted public firms are more vulnerable to Mergers and Acquisitions